Growth and Survival of Clarias gariepinus Fry Raised on Plankton from Cow Dung and Poultry Manure - Ogunremi, J.B.; Obasa, S.O. (Pakistan Journal of Nutrition, 2009)
The effect of zooplankton raised from cow dung and poultry dropping on the growth and survival or Clarias gariepinus fry was investigated weighing 0.01 g ± and length ± 7.00 mm. Among the treatments, poultry manure source of zooplankton used for feeding fry six times daily had the highest specific growth rate 7.45, mean percentage body weight gain 45% and survival rate 53.33%. In terms of mean length gain, treatment fed nine times daily had the highest 2.88 mm. The specific growth rate and mean length gained were significant (p<0.05) where as the values for mean weight gained and mean length increase were insignificant (p>0.05). The survival rate for the period were found to be the same for treatments where fry were fed nine times daily with different food sources, also applicable to treatment fed thrice daily with poultry manure as the source.